Endodontics versus implantology: To extirpate or integrate? - Dawson, Anthony S.; Cardaci, Santo C. (Australian endodontic journal, 2006)
An increasingly frequent dilemma in restorative dentistry is the question of whether to retain a badly damaged tooth and restore it, or to remove and possibly replace it. Given the ethical difficulties inherent in testing this question, it is unlikely that we will ever see a properly designed clinical trial that will provide an answer. One of the most strongly debated components of this question is whether endodontic treatment and restoration can compete with a dental implant‐borne prosthesis in terms of longevity and success. In the current paper, the authors will attempt to: (i) answer this question based on our current understanding of the dental literature; and (ii) provide practitioners with guidelines that might be applied to their daily practices.